Under the medical gaze : facts and fictions of chronic pain - Greenhalgh, Susan (Berkeley : University of California Press, 2001)
This compelling account of the author's experience with a chronic pain disorder and subsequent interaction with the American health care system goes to the heart of the workings of power and culture in the biomedical domain. It is a medical whodunit full of mysterious misdiagnosis, subtle power plays, and shrewd detective work.
Understanding Chronic Pain -- Problematique -- Prologue: Finding Dr. Right -- Doing Biomedicine -- The Initial Consultation: The Making of a "Fibromyalgic" -- Medicating the "Fibromyalgic"-Arthritic Body -- Producing the Good Patient -- Doing Gender -- A Most Pleasant Patient -- Silent Rebellion and Rage -- A Depression Worse than the Disease -- A Losing Battle to Get Better -- Struggling to Make the Treatment Work -- "Accept It!" Alternative Medicines Offer Medicine for the Mind -- A Life Shrunk, a Mind Gone Nearly Mad -- Rebellion and Self-Renewal -- A Second Opinion: The Unmaking of a "Fibromyalgic" -- The Final Meeting: A Tale of Decline and a Denial -- Out from under the Medical Gaze -- Narrating Illness, Politicizing Pain -- Conclusion: Re-viewing the Medicine of Chronic Pain -- Epilogue: Speaking of Pain--On Stories, Cultural Recuperations, and Political Interventions.
Includes bibliographical references (pages 345-364) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Greenhalgh, Susan -- Health; Greenhalgh, Susan; Greenhalgh, Susan; Chronic pain -- Patients -- United States -- Biography; Arthritis -- Patients -- United States -- Biography; Fibromyalgia -- Patients -- United States -- Biography; Physician and patient; Diagnostic errors; Pain; Arthritis; Chronic diseases; Fibromyalgia; Pain; Arthritis; Chronic Disease; Diagnostic Errors; Fibromyalgia; Physician-Patient Relations; Douleur chronique -- Patients -- États-Unis -- Biographies; Fibromyalgie -- Patients -- États-Unis -- Biographies; Relations médecin-patient.; Erreurs de diagnostic; Douleur; Arthrite; Maladies chroniques; Fibromyalgie; HEALTH & FITNESS -- Pain Management; MEDICAL -- Pain Medicine; Pain; Fibromyalgia; Chronic diseases; Arthritis; Arthritis -- Patients; Chronic pain -- Patients; Diagnostic errors; Fibromyalgia -- Patients; Health; Physician and patient; United States; Chronischer Schmerz; Patient; Fibromyalgie; Rheumatoide Arthritis; Arzt; SOCIAL SCIENCE / Anthropology / General; alternative medicine; american health care; biomedical; chronic disease; chronic pain; cultural studies; detective; diagnosis; disease; ethnography; feminism; feminist; fibromyalgia; health and wellness; health care system